2020
DOI: 10.1038/s41390-020-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain metabolism contributes to executive function deficits in school-aged children born very preterm

Abstract: Background Executive function deficits in children born very preterm (VPT) have been linked to anatomical abnormalities in white matter and subcortical brain structures. This study aimed to investigate how altered brain metabolism contributes to these deficits in VPT children at school-age. Methods Fifty-four VPT participants aged 8–13 years and 62 term-born peers were assessed with an executive function test battery. Brain metabolites were obtained in the frontal white matter and the basal ganglia/thalami, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…Recent research demonstrated that mI can cause glial cells differentiation, and that the elevation of the mI/Cr ratio is often interpreted to reflect glial cell activation (Schnider et al, 2020). With a focus on changes in immunofluorescence staining results after CLP surgery, we observed that microglial cells activated in the hippocamp of SAE rats, which supported the hypothesis The ALFF values and metabolites in the hippocampus were negatively correlated with duration in the target quadrant.…”
Section: Discussionsupporting
confidence: 83%
“…Recent research demonstrated that mI can cause glial cells differentiation, and that the elevation of the mI/Cr ratio is often interpreted to reflect glial cell activation (Schnider et al, 2020). With a focus on changes in immunofluorescence staining results after CLP surgery, we observed that microglial cells activated in the hippocamp of SAE rats, which supported the hypothesis The ALFF values and metabolites in the hippocampus were negatively correlated with duration in the target quadrant.…”
Section: Discussionsupporting
confidence: 83%
“…inhibition, cognitive flexibility, working memory, verbal and nonverbal fluency and problem solving) and associated sub-tests. However, mean executive function composite scores have been used previously to demonstrate associations between neurological correlates and executive function ( Nosarti et al , 2008 ; Wehrle et al , 2017 ; Schnider et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A global score derived from an extensive test battery was used under the assumption that executive function is a multi-dimensional construct including different cognitive processes that can be distinguished but which are correlated [see systematic review by ( Baggetta and Alexander, 2016 )]. Using a mean composite score further decreases multiple testing and associated Type 1 errors and has been successfully applied in other neuroimaging studies in at risk populations ( Nosarti et al , 2008 ; Wehrle et al , 2017 ; Schnider et al , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The EpoKids study is an ongoing follow-up study investigating the long-term effect of early erythropoietin administration on executive functions in children born between 26 and 32 weeks of gestational age 17 . The current analysis uses data on the subgroup of children who were assessed between 2017 and 2019 (for details, see 18 ). The Neuropsychology and Memory (NEMO) research programme was run between 2011 and 2015 and assessed cognitive development and training-induced improvements of cognitive abilities in school-aged children born before 32 weeks of gestational age or with a birth weight below 1500 grams 19 .…”
Section: Methodsmentioning
confidence: 99%